Scaffolding Reflective Practice through VR-Mediated Mentoring of Teachers - Paulsen, Lucas; Dau, Susanne (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Novice teachers often struggle navigating the complexities of in-service teaching practices when transitioning from education and practice, leaving them feeling unprepared without support structures. Tool-based mentoring can scaffold reflective practice by enabling teachers to collaboratively analyse video-recorded teaching episodes, supporting professional development, self-efficacy, and well-being. This study examines the use of collaborative 360-degree video in virtual reality (360VR) as a reflective mentoring tool for novice teachers in Danish primary and lower-secondary schools. Grounded in Reflective Practice-Based Learning (RPL) and situated within a broader design-based research (DBR) project, the study focuses on how teachers and mentors experience and reflect on the potentials and limitations of immersive technologies for scaffolding shared reflection around classroom management situations. Following each VR-mediated mentoring session, participants engaged in structured debriefing interviews, which have been thematically analysed. Four themes emerged from the analysis (1) immersion allows for re-experiencing authentic situations, (2) shared immersion affords multiple perspectives, (3) cycles of action and reflection link VR and practice, and (4) implementation perspectives. Findings highlight the potential of collaborative 360VR to mediate and scaffold reflective practice by creating create an immersive, shared space for reflective dialogue. The findings however also highlight technical and organisational challenges in terms of implementation. By engaging with participants' reflections during debriefings, this paper contributes to ongoing discussions about using immersive technologies to support newly graduated professionals' development through reflective practice.